Factors affecting learner engagement in HyFlex learning environments - Yingyi, Xu; Razak, Rafiza Abdul; Halili, Siti Hajar (International Journal of Evaluation and Research in Education (IJERE), 2024)
Higher education institutions are increasingly implementing hybrid flexible (HyFlex) learning mode due to its accessibility and flexibility. However, little is known about students’ engagement and potential predictors in this learning approach. This study’s objective was to look into strategies for enhancing learner engagement in HyFlex learning environments. In this study, the relationships between specific predictors (learner control, self-efficacy, and learning motivation), learners’ perceived community of inquiry (CoI) presences, and learner engagement in HyFlex learning environments were investigated using partial least squares structural equation modeling (PLS-SEM). In order to collect data on the study’s variables, an online survey was completed by 367 students who were enrolled in the HyFlex learning environments at a Chinese college. The results indicated a direct and positive relationship between learner engagement and factors such as self-efficacy, learner motivation, and learners’ perceived CoI presences. However, learner control did not have a direct and positive impact on learner engagement. Instead, it indirectly influenced learner engagement by affecting learners’ perceived CoI presences. In addition, the relationships between learner motivation and engagement, as well as self-efficacy and learner engagement, were significantly mediated by the learners’ perceived CoI presences. The findings offer fresh perspectives on the roles of learner control, self-efficacy, learner motivation, and learners’ perceived CoI presences in HyFlex learning, with implications for learning processes and learner engagement.